PEMBERDAYAAN PETANI RUMPUT LAUT DALAM PENGEMBANGAN EKOWISATA DI DESA LEMBONGAN KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - I Kadek Agus Suwandana (Forum Manajemen, 2015)
Less understanding of tourism culminate with the helplessness ofseaweed farmers in facing tourism development. To determine the plan in achievinga solution, then it is divided into three issues such as: (1) How does the shape androle of each stakeholder in the empowerment of seaweed farmers and developmentof existing ecotourism. (2) What benefits are obtained by seaweed farmers in thedevelopment of ecotourism .Empowerment theory, the active community andstructural-functional theory were used to dissect the problem. The qualitativedescriptive method of data collection techniques through observation, interview, andliterature reviews. The data collected were analyzed by descriptive qualitative andtransforming the raw data in the form of fixed data, easy to understand, interpreting,and presenting the information presented as principal study. The results showedthe empowerment of seaweed farmers in the village of Lembongan requires therole of all relevant stakeholders through a partnership which is formed to provideeconomic and social benefits for the community. The seaweed farmers have to begiven training in managerial, financial aid and supporting infrastructures. Afterthe independence of seaweed farming community has been considered adequate,the system of partnerships and mentoring by stakeholders gradually reduced. Thisresearch is also expected to be used as input for the government, tourism industry,and the seaweed farmers in the development of ecotourism, as well as for academicsand practitioners are expected to conduct further research.